Togo: Politics, economy and society in 2009 - Dirk Kohnert (Africa Yearbook Volume 6: Politics, Economy and Society South of the Sahara in 2009, 2010)
Domestic politics in Togo in 2009 was dominated by the preparation for the decisive 2010 presidential elections and by the aggravating family feud within the ruling Gnassingbé clan. In April, the latter culminated in an alleged coup plot of Kpatcha Gnassingbé, the junior half-brother of the Head of State, which involved also other members of the 'family' which were imprisoned without official arraignment until the end of the year. The international donor community rewarded political reforms. Economic growth was negatively affected by the global economic and financial crisis. – – Die Innenpolitik Togos war 2009 geprägt von der Vorbereitung der entscheidenden Präsidentschaftswahlen 2010 und von der sich verschärfenden Familienfehde innerhalb des herrschenden Gnassingbé-Clans. Letztere gipfelte im April in einem angeblichen Putschversuch von Kpatcha Gnassingbé, dem jüngeren Halbbruder des Staatschefs, in den auch andere Mitglieder der ,,Familie“ verwickelt waren, die bis Jahresende ohne offizielle Anklageerhebung inhaftiert blieben. Die internationale Gebergemeinschaft belohnte politische Reformen. Das Wirtschaftswachstum wurde durch die globale Wirtschafts- und Finanzkrise negativ beeinflusst.
Additional information: Author's version
Keywords: F35; F54; N47; Z13; 330; Togo; Africa Yearbook 2009; domestic policy; foreign affairs; socio-economic development; period under review 2009